Entrepreneurship and green finance practices : avenues for sustainable business start-ups in Asia - Raza, Syed Ali; Tunio, Muhammad Nawaz; Ali, Muhammad; Puah, Chin-Hong (Emerald Publishing Limited, 2023)
Environmental sustainability is the future of business. To achieve sustainable development and gain a competitive advantage in the business world, companies must adapt new practices to 'go green.' While market leader China has implemented a 'New Infrastructure' plan to increase green growth, investing $2.6 trillion in renewable energy and introducing a five-year economic plan focusing on technology and innovation, Southeast Asia is far behind. Entrepreneurship and Green Finance Practices focuses on critical issues such as the role of Green Financing in Green Entrepreneurship in Asian Countries and looks for the mechanisms that can help in idea-generation and the launching of successful Green Start-ups. Green entrepreneurs can address environmental challenges, create new solutions, act as drivers for sustainable growth and serve as a source of motivation for others. Moreover, the entrepreneurship initiated on sustainable production and consumption can help better manage resources, resulting in economic growth. The concept of adopting green practices opens new dimensions of thinking for businesses and creates new opportunities for entrepreneurs - Entrepreneurship and Green Finance Practices is invaluable for social scientists, students, academicians, academic institutions, policymakers, and other related stakeholders.